Distribution of Myocardial Infarction Regarding Hypertensive, Diabetes and Gender - Sadia Menhas, Muhammad Shehryar, Muhammad Saad, Aizaz Afridi, Nayab Ali, Ajmal Khan, Muhammad Imran (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Coronary artery disease is the leading cause of death throughout the entire world, in Pakistan most common type of coronary disease is the myocardial infarction. Regarding the frequency of risk factors most common location of MI is anterior and inferior wall infarction in male and female, hypertensive and diabetic patients. The aims of this study was to determine the type, site, and risk factors in myocardial infarction patients associated with gender, diabetes and hypertension. Method: cross sectional study was conducted in CCU and in cardiology ward at Lady Reading Hospital Peshawar. The duration of this study was four months i.e from March 2019 to June 2019. From 18 to 100 years old data were collected on the basis of convenient sampling technique. The data was collected through a standard performa and was analyzed through SPSS 23. Results: Highest number of cases were found in age group 51-75 years with 60.4%. Male patients (56.8%) were more affected than females. Married persons were frequently suffered from myocardial infarction with 99.1%. Among total myocardial infarction patients 78.4% were suffered from ST segment elevation. Anterior side of heart were affected more with MI, followed by inferior side. Myocardial infarction were common among hypetensive patients. Family history of hypertension was also higher among the myocardial infarcted patients. Low level of diabetes were also found among myocardial infarcted patients. A total of the 227 infarction patients 75.3% patients having ST segment elevation were recorded on ECG. Conclusion: Frequency of MI is higher in male, hypertensive patients and STEMI were most common type of MI, anterior and inferior wall MI is the most common location of MI among gender, diabetics and hypertensive patients. A risk factor that is extremely powerful in one nation may not be as significant in another due to differences in the incidence of risk factors in various populations. Keywords: Coronary artery disease, myocardial infarction, type of MI, site of MI, Hypertension, Diabetes, Family History.